Weight Selection Attempts of Elite Classic Powerlifters. Issue 1 (February 2021) - Travis, S. Kyle; Zourdos, Michael C.; Bazyler, Caleb D.
This study provides the first comparison of weight selection attempt strategies used by powerlifters competing at the international level. We observed attempts selected by elite male and female classic powerlifters and compared weight selection attempts between sexes. Male (n = 66) and female (n = 43) powerlifters who completed all lifts successfully at an International Powerlifting Federation Classic World Championship between 2012-2019 were included in the analysis. We calculated the percentage weight increase from first attempts (A1) to second attempts (A2) and from A2 to third attempts (A3). For purposes of comparison, A1 values were expressed as a percentage of A3 values. We calculated non-parametric statistics with effect sizes for between and within-group comparisons. Relative to A3, males selected greater A1s compared to females for bench press (η 2  = 0.16; p  = 0.004) and deadlift (η 2  = 0.06; p  = 0.036) for each lift. Alternatively, females selected greater A1 to A2 and A2 to A3 progressions for bench press (η 2  = 0.06; p  = 0.026; η 2  = 0.21; p  = 0.005, respectively), and A2 to A3 for deadlift (η 2  = 0.04; p  = 0.035) compared to males. Within-group comparisons showed that males selected greater A1s on bench press compared to deadlift (η 2  = 0.06; p  = 0.046), whereas females selected greater A1s on squat compared to deadlift (η 2  = 0.13; p  = 0.038) relative to A3. Males also selected greater A2 to A3 progressions on deadlift compared to bench press (η 2  = 0.10; p  = 0.044), whereas females selected greater A2 to A3 progressions for bench press (η 2  = 0.15; p  = 0.039) and deadlift compared to squat (η 2  = 0.10; p  = 0.041). In conclusion, selecting an opener of ∼91% of the expected A3 weight, followed by ∼5% increase from A1 to A2, and ∼3% increase from A2 to A3 represent the typical weight selection attempts used across lifts by elite classic powerlifters competing in the World Championships. The results of this study provide novel insight into the weight selection attempts of elite classic powerlifters.